Assessment of mechanical engineering final year projects using fuzzy multi attribute utility theory - Dong, Chensong (Murdoch University, 2012)
This paper presents an assessment method for the final year project theses of mechanical engineering students using Fuzzy Multi-Attribute Utility Theory (FMAUT). All the staff members' opinions of thesis assessment are utilised to form an expert database. The ratings given by the supervisor and assessor are conveniently converted into the final thesis mark with the aid of the developed approach. The advantages are increased clarities and reduced discrepancies. An example is given to illustrate the approach.